2009
DOI: 10.1111/j.1479-8301.2009.00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of behavioral and psychological symptoms of dementia in long‐term care facilities in Japan

Abstract: Background: An increasing number of old people, and their medical requirements, cannot be managed by their families in their homes, which has been the traditional and prevalent practice in Japan. The number of people with dementia is increasing and behavioral and psychological symptoms of dementia (BPSD) make care difficult. In the present study, we investigated management techniques for BPSD in long-term care facilities in Japan by using the data mining method, which looks at the reported behaviors of care pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Behavioral therapy, 10 aromatherapy 11 and animal‐assisted therapy 12 are sometimes useful. Different strategies are recommended by the clinical settings either at home 13 or in institutions, 14,15 targeting each type of dementia, including Alzheimer's disease (AD), 2 frontotemporal dementia, 16 diffuse Lewy body disease, 17 and vascular dementia 18 …”
mentioning
confidence: 99%
“…Behavioral therapy, 10 aromatherapy 11 and animal‐assisted therapy 12 are sometimes useful. Different strategies are recommended by the clinical settings either at home 13 or in institutions, 14,15 targeting each type of dementia, including Alzheimer's disease (AD), 2 frontotemporal dementia, 16 diffuse Lewy body disease, 17 and vascular dementia 18 …”
mentioning
confidence: 99%
“…Considering the limitations of the drugs available, clinicians should be prepared for the progression of the disease of the patients in the long run. Controlling of behavioral and psychological symptoms of the patients is important for the family and caregivers of the patients 11,18,25–29 . Non‐pharmacological intervention, 12–14,30 a care program, 31 and support of the patients and family 19,32 will be even more important for the treatment of Alzheimer's disease patients.…”
Section: What Clinicians Should Know To Serve Alzheimer's Patients Bementioning
confidence: 99%
“…The number of Alzheimer's disease patients in Japan is expected to increase to 1.42 million in 2015, 1.67 million in 2020, and 2.2 million in 2025. The prevalence of Alzheimer's disease has increased the need for research aimed at identifying the risk, 3,4 pathogenesis, 5–8 diagnosis, 9 drugs, 10,11 non‐pharmacological intervention, 12–15 care, 16–18 and support 19,20 for this disease. A diverse range of compounds has been evaluated as potential treatments for Alzheimer's disease, and five compounds have been approved in the world for the treatment of Alzheimer's disease.…”
mentioning
confidence: 99%
“…Behavioral therapy (Narumoto et al , 2009), aromatherapy (Jimbo et al , 2009) and animal‐assisted therapy (Le Roux & Kemp, 2009) are sometimes useful. Different strategies are recommended by the clinical settings, either at home (Kinoshita, 2008) or in institutions (Kutsumi et al , 2009; Tanaka et al , 2009). In view of specific features of Alzheimer's disease (Amano et al , 2009), frontotemporal dementia (Kimura et al , 2009), diffuse Lewy body disease (Kosaka, 2008), and vascular dementia (Chen et al , 2008), some unique trials have been reported.…”
Section: Introductionmentioning
confidence: 99%